Flags for seeking help: making supervisor expectations of general practice trainee help-seeking explicit. Issue 2 (4th March 2021) - Sturman, Nancy; Fitzmaurice, Liz; Lee, Cathy; Sheldrake, Michelle; Ingham, Gerard
ABSTRACT: Timely supervisor input into patient care plays a key role in ensuring the safety of patients under the care of general practice trainees. Current models of clinical supervision for trainees in both hospital and general practice training have, however, been criticised for placing too much onus on the trainee to request assistance, despite the many known barriers for trainees to do so. An important barrier to general practice trainee help-seeking is trainee uncertainty about when and how their clinical supervisor expects them to seek this assistance. We introduce a tool, 'Flags for Seeking Help', which was modified from an existing checklist, to assist supervisors to tailor their input to the care of their trainee's patients. The tool aims to make supervisor expectations of trainees explicit, including when trainees should request assistance during consultations (rather than defer this until more convenient opportunities) and when this assistance should be face-to-face (rather than by phone or messaging systems). Our aim is to reduce the barriers for trainees to request in-consultation and face-to-face supervision, in particular, when it is indicated. We outline the evidence which informed the development of the tool, and present some preliminary findings from a pilot in Australian general practice training.